2017
DOI: 10.1177/1476750317741352
|View full text |Cite
|
Sign up to set email alerts
|

Using photovoice to develop critical awareness of tobacco environments for marginalized youth in California

Abstract: Photovoice is used widely for engaging community members in action research aimed at reducing health inequities. Photovoice methodology can help to raise participants’ critical awareness regarding the root causes of community health problems, thereby encouraging them to take action to address these root causes. We report on our experiences using photovoice as part of a tobacco prevention project with multiethnic youths in an underresourced Northern California community. Through an iterative cycle of action and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In Photovoice, participants can use disposable, digital, or smartphone cameras to take photos in response to a photo-taking or question prompt. After a photo-taking period, researchers engage participants in photo elicitation interviews or focus groups, contextualizing what they chose to photograph and why ( Wang & Burris, 1997 ; Wang, 1999 ; Glenis & Boulton, 2017 ; Lee et al, 2019 ; Baig et al, 2019 ; Cheezum et al, 2019 ; Lofton et al, 2020 ; Aparicio et al, 2021 ; Craft-Blacksheare et al, 2021 ; Feingold et al, 2021 ; Morrow et al, 2022 ; Bood et al, 2022 ; Jackson et al, 2022 ). Researchers may use sets of guided discussion questions with participants to learn more about their photos.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Photovoice, participants can use disposable, digital, or smartphone cameras to take photos in response to a photo-taking or question prompt. After a photo-taking period, researchers engage participants in photo elicitation interviews or focus groups, contextualizing what they chose to photograph and why ( Wang & Burris, 1997 ; Wang, 1999 ; Glenis & Boulton, 2017 ; Lee et al, 2019 ; Baig et al, 2019 ; Cheezum et al, 2019 ; Lofton et al, 2020 ; Aparicio et al, 2021 ; Craft-Blacksheare et al, 2021 ; Feingold et al, 2021 ; Morrow et al, 2022 ; Bood et al, 2022 ; Jackson et al, 2022 ). Researchers may use sets of guided discussion questions with participants to learn more about their photos.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers may use sets of guided discussion questions with participants to learn more about their photos. In studies that have used Photovoice, transcripts of oral narratives from sharing and reflecting on photographs taken for the study as well as other forms of participant-generated text such as journal entries ( Glenis & Boulton, 2017 ; Morrow et al, 2022 ) or photo captions ( Bood et al, 2022 ; Jackson et al, 2022 ; Lee et al, 2019 ) are coded in tandem with photography; of note, some studies, aligned with the participant empowerment underpinnings of Photovoice, engage participants in the analytic or photo-sorting process ( Glenis & Boulton, 2017 ; Jackson et al, 2022 ; Lofton et al, 2020 ; Morrow et al, 2022 ). Bood et al reported how the “first author described what could be seen on the photo and then applied codes to the photo and caption” (p. 3355).…”
Section: Literature Reviewmentioning
confidence: 99%